A orientação da ação de controle na resolução de problemas matemáticos em professores: uma experiência formativa à luz da Teoria de P. Ya. Galperin - Gonçalves, Paulo Gonçalo Farias (2020)
The increasing ease and speed of access to information provided by scientific and technological improvements obtained throughout human history, has required the current individual, among other things, to know how to organize their learning processes in an independent, conscious and reflective way, that is, to learn to learn according to the Historical-Cultural Approach. Among the necessary conditions for this, the control in solving mathematical problems has been pointed by the investigations as a little-explored component in the context of mathematics learning. Therefore, the present thesis aims to study the influence of a Formative Experience in the reworking of the control action orientation in solving mathematical problems of undergraduate students. This study was developed at the Instituto de Formação de Educadores (IFE), campus of the Universidade Federal do Cariri (UFCA) in the Brejo Santo-CE city, it was attended by eight students of undergraduate courses. If constituted as a Formative Experience research, the data collection instruments used were: observation, pedagogical test, students' diary and the questionnaire. The data were explored according to a Content Analysis. From the initial diagnosis, we found that the graduates participating in the Formative Experience did not have an appropriate understanding of the control action. From then on, a Formative Experience was elaborated and developed, in the light of the Planned Theory of Mental Actions and Concepts Formation, in which it was possible to observe changes in students' awareness of the relevance of control orientation as a guide for better understanding and mitigation of errors during the process of solving mathematical problems. The processes of verification and adjustment of human action that constitute the control of learning, become this cognitive ability a relevant component of the personality of a 21st century individual. Furthermore, is of utmost importance that more research is to carry out on the subject, aiming at the proliferation of more educational practices that discuss this component and contribute to the formation of autonomous learners.